Implementasi Aplikasi Toko Creative Card Berbasis Website Menggunakan Metode Waterfall - Yusuf Aprianto (Pusat Riset dan Inovasi Nasional, 2024)
The development of technology and the internet has triggered a significant transformation in consumer behavior, especially in the context of electronic commerce. This research aims to address growing market needs by developing a web-based online sticker shop application. This application is designed to provide convenience in the process of selling and purchasing stickers, optimize user experience, and increase product accessibility via online platforms. The development method used in this research involves the application of web technologies such as HTML, CSS, JavaScript, and PHP. This approach allows building systems in a structured and organized manner, with a focus on features that support intuitive user interaction. Some of the key features implemented include informative product pages, an efficient shopping cart system, and transaction history to provide transparency and order tracking for consumers. The result of this research is an online sticker shop application that not only makes the sales process easier for sellers, but also provides a comfortable online shopping environment for buyers. It is hoped that this application can increase efficiency in sales management, increase the competitiveness of the sticker business, and make a positive contribution to the growth of the e-commerce industry. As an innovative solution, this application is expected to be able to keep up with market trends and provide a satisfying online shopping experience for users.